Ringed esophagus: all that glitters is not gold - Freidenson-Bejar, Jeffrey (2024)
We report the case of an elderly patient with progressive dysphagia to solids and later to liquids, and weight loss. The patient underwent an upper endoscopy, which showed multiple stenoses and trachealization. Biopsies were taken and a diagnosis of lymphocytic esophagitis was made. Pneumatic dilation to 12 mm was performed, and the patient recovered with no recurring symptoms. Dysphagia in the elderly should not be overlooked, and physicians should consider lymphocytic esophagitis as a differential diagnosis.